In situ soil reclamation by air stripping and sludge uptake - Cardenosa, Mauricio; Autenrieth, RobinL; Bonner, JamesS (Journal of hazardous materials, 1989)
A laboratory-scale study was conducted to evaluate the feasibility of an in situ reclamation technique for contaminated soils by combining soil stripping techniques and in situ soil surface biodegradation. By pumping air at the base of a test column, a volatile organic compound (VOC) in the soil was mobilized through the soil and trapped in a thin layer of dried activated sludge. The contaminant, once trapped in the sludge blanket, would be available for biological degradation by the sludge microorganisms. Test soil consisted of a homogeneous sand with a moisture content less than 0.5% and particle diameters smaller than 0.84 mm. Dried sludge, obtained from a municipal waste-water facility, was blended until the particle size characteristics were consistent with the sand. Experiments were initiated by passing air saturated with toluene throught the soil column until equilibrium. The initial concentration of toluene was approximately 700, μg per gram of sand. Clean air was then forced through the system to mobilize the toluene at rates which ranged between 1 and 2.7 pore volumes per minute. Over 95% of the particle-bound toluene was removed from the sand within six hours of stripping. On a mass-per-mass basis, the sludge sorbed approximately 70% of the mobilized toluene. The combination of air stripping techniques and use of a sludge blanket to reduce volatile emissions from the soils is feasible and merits further research. Studies to investigate the biodegradation potential of the sludge blanket for toluene and trichloroethylene will be the subject of investigation for future research.